2021
DOI: 10.1371/journal.pone.0253755
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of rice varieties, organic manure and water management on greenhouse gas emissions from paddy rice soils

Abstract: The study is focused on impact of manure application, rice varieties and water management on greenhouse gas (GHG) emissions from paddy rice soil in pot experiment. The objectives of this study were a) to assess the effect of different types of manure amendments and rice varieties on greenhouse gas emissions and b) to determine the optimum manure application rate to increase rice yield while mitigating GHG emissions under alternate wetting and drying irrigation in paddy rice production. The first pot experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 82 publications
3
17
1
Order By: Relevance
“…Therefore, they are considered as key contributors to global climate change. Applying organic amendments and inorganic fertilizers in paddy fields can increase GHG emissions but vary with external factors, such as climate, soil properties, rice varieties, and land management practices [ 26 ]. In addition, both GHGs may represent different responses to prolonged submergence conditions of the rice fields.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, they are considered as key contributors to global climate change. Applying organic amendments and inorganic fertilizers in paddy fields can increase GHG emissions but vary with external factors, such as climate, soil properties, rice varieties, and land management practices [ 26 ]. In addition, both GHGs may represent different responses to prolonged submergence conditions of the rice fields.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, organic agricultural practices are attracting attention in relation to eco-friendly farming, soil conservation, and economic feasibility [ 2 ]. Many previous experimental studies have demonstrated that the long-term application of SOA in paddy fields would bring benefits to sustainable rice production [ 24 , 25 , 26 ]. These attempts have been applied to many paddy fields in South Korea over the past decades.…”
Section: Introductionmentioning
confidence: 99%
“…Although the measurement of GHGs emissions from rice cultivation have been systemically researched by a number of regional countries in South East Asia, there is no reliable information available from Myanmar, especially CH4 and N2O emissions, from existing farmers' adopted fertilizer application under different rice establishment methods (Win et al, 2021). Further, the insight upon the consequences of the local farmers' adopted agricultural practices on CH4 and N2O emissions from rice cultivation was gained from this study.…”
Section: Emissions Pattern Of Ch4 and N2omentioning
confidence: 91%
“…Adopting water conservation and management practices in agriculture enable farmers to overcome situations such as droughts (Das et al, 2009;Devi, 2018;Mandal and Singha, 2020). Mid-season drainage/ alternate wet and dry method of irrigation is reported to reduce methane emissions from rice fields (Manjunath et al, 2009;Li et al, 2018;Surendran et al, 2021;Win et al, 2021). Techniques such as adjustment of sowing time, double transplanted rice, direct seeded rice, aerobic rice, and System of Rice Intensification (SRI) are found to be effective in sustaining rice production in a changing climate (Goswami et al, 2016;Uphoff and Thakur, 2019;Mandal and Singha, 2020;Assefa et al, 2021).…”
Section: Climate-induced Hazard Mitigation and Adaptation Strategies ...mentioning
confidence: 99%